Evaluating the skill of seasonal forecasts of sea ice in the Southern Ocean: insights from the SIPN South project 2017-2022 - Massonnet, F; Reid, P; Lieser, J; Bitz, C; Fyfe, J; Hobbs, W (., 2022)
The SIPN South project is an international, coordinated initiative endorsed by the Year Of PolarPrediction (YOPP), that aims at identifying the skill of current seasonal predictions of sea icearound Antarctica. Here, we review and analyze the results of five years of predictions of summersea ice conducted by 20 groups since 2017, having contributed together more than 1000 forecasts.A wide range of approaches is considered, ranging from statistical data-driven to dynamicalprocess-based models. We evaluate the ability of the forecasts to reproduce observed sea ice areaat the circumpolar and regional levels and their skill relative to trivial forecasts (climatology,persistence). We find that a substantial spread exists already at day one in the dynamicalforecasts, pointing at problems with the initialization. We also find that the forecasts based onstatistical modeling perform generally better than forecasts based on dynamical modeling.